Climate Warming and Occupational Heat and Hot Environment Standards in Thailand - Wantanee Phanprasit; Kannikar Rittaprom; Sumitra Dokkem; Aronrag C. Meeyai; Vorakamol Boonyayothin; Jouni J.K. Jaakkola; Simo Näyhä (Elsevier, 2021)
Background: During the period 2001 to 2016, the maximum temperatures in Thailand rose from 38-41oC to 42-44oC. The current occupational heat exposure standard of Thailand issued in 2006 is based on wet bulb globe temperature (WBGT) defined for three workload levels without a work-rest regimen. This study examined whether the present standard still protects most workers. Methods: The sample comprised 168 heat acclimatized workers (90 in construction sites, 78 in foundries). Heart rate and auditory canal temperature were recorded continuously for 2 hours. Workplace WBGT, relative humidity, and wind velocity were monitored, and the participants' workloads were estimated. Heat-related symptoms and signs were collected by a questionnaire. Results: Only 55% of the participants worked in workplaces complying with the heat standard. Of them, 79% had auditory canal temperature ≤ 38.5oC, compared with only 58% in noncompliant workplaces. 18% and 43% of the workers in compliant and noncompliant workplaces, respectively, had symptoms from heat stress, the trend being similar across all workload levels. An increase of one degree (C) in WBGT was associated with a 1.85-fold increase (95% confidence interval: 1.44-2.48) in odds for having symptoms. Conclusion: Compliance with the current occupational heat standard protects 4/5 of the workers, whereas noncompliance reduces this proportion to one half. The reasons for noncompliance include the gaps and ambiguities in the law. The law should specify work/rest schedules; outdoor work should be identified as an occupational heat hazard; and the staff should include occupational personnel to manage heat stress in establishments involving heat exposure.